Religiousness of academic students as a determinant of the psycho-social functioning Part II. Religiousness as a determinant of the choice of strategy and forming the attitudes toward self and world - Wysocka, Ewa (Paedagogia Christiana, 2008)
In the presented paper there are realized the analysis related to the strategies of coping with the crisis situation practiced by the university students. The mentioned strategies represent the different character – from the constructive actions – the purpose of which is resolving the problems, by the differently directed withdrawing actions (emotional and intellectual distance), to the social support searching. There are exposed to the analysis also life patterns represented by youths, which are the result of the dominating life experiences of the individual: the positive attitude – developmental (“I am OK, you are OK”), which is connected with conformism being expressed as a mechanism of the social adaptation, and indicated the correct adaptation and disintegrating the development patterns – personal disintegration (“I am not OK, you are OK”) which is connected with neuroticism, self-accusation, indicating the disintegration at the personal level, multi-level disintegration (“I am not OK, you are not OK”) connected with the nihilism pattern, withdrawal, abnegation, determining the disintegration in the personal dimension (translocated aggression, self-devaluation) as well as in the social one (world-devaluation), disintegration of the relation “me–world” (“I am OK, you are not OK”) connected with egocentrism, aggression directed outside and rebellion against the world that can mark a tendency to its deconstruction. The type of the coping strategies and life attitudes were analyzed in the context of the declared religious patterns character, that allowed to put forward a thesis, that religiousness is an important determinant of the preferred coping strategies as well as shaping the life patterns of the youths.